A Physical-Constrained Decomposition Method of Infrared Thermography: Pseudo Restored Heat Flux Approach Based on Ensemble Bayesian Variance Tensor Fraction; IEEE Transactions on Industrial Informatics; Vol. 20, iss. 3 - Hongjin Wang; Yuejun Hou; Yunze He; Can Wen; Giron-Palomares B. Benjamin; Yuxia Duan; Bin Gao; Vavilov V. P. Vladimir Platonovich; Yaonan Wang (2024, 2024)
Title screen